Displacement of Manuscripts, Printing Revolution and Rediscovering Islamic Classics - Din, Mehraj (Religion & theology, 2021)
Taking as the starting point, Ahmed El-Shamsy’s new book Rediscovering the Islamic Classics is a comprehensive introduction to trace the historical trajectory of Islamic intellectual legacy. In this engaging yet pleasantly thought-out book El Shamsy intends to offer a fresh conversation on the massive loss of manuscripts, role of colonialism and its role in strengthening the Orientalist enterprise in Muslim World including the drain of manuscripts into Europe. Bringing to light the agents and events of the Islamic print revolution, this work is also an absorbing examination of the central role printing and its advocates played in the intellectual history of the modern Arab world. This review essay offers a contextual perspective and a detailed rationale behind the loss of manuscripts and unpacks some of the important debates behind the decline and restoration of Islam’s intellectual legacy.